Linking plant strategies and ecosystem function: an assessment of the contribution of biodiversity to neotropical grassland productivity - Ospina Hernández, Sonia D. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE) Bangor University, Gwynedd (RU), 2014)
Tesis (Ph. D.) -- CATIE: Escuela de Posgrado, Turrialba (Costa Rica), Bangor University, 2011